(untitled) - Barg, U.C. (Rome, 1992)
The document is directed to acquaculture development specialists, coastal resource use planners and government officials involves and interested in the planning and management of coastal aquaculture development within the wider context of resource use incoastal areas.
Keywords: Aquaculture,Environmental management,Nuôi trồng thủy sản